Educação para sustentabilidade: contribuições para o desenvolvimento do tema em pós-graduações em administração - Marques, Carolina Sampaio (2016)
Education for Sustainability is seen as a powerful change and social transformation tool aimed at greater equity in relations between society and the environment. Thus, this dissertation aims to analyze the scenario of Education for Sustainability in cur¬sos Graduate Sensu stricto in Rio Grande do Sul State Administration - Brazil. For this, the nine master's programs in existing Administration in Rio Grande do Sul were searched. In terms of methodological procedures, a descriptive and exploratory research of qualitative nature was carried out to meet four distinct stages: i) analyze the pedagogical projects of the nine courses, covering characterization of the subjects and relations with sustainability in the curriculum; ii) the documentary analysis of all 1813 dissertations have been published in the gauchos masters, seeking to relate these documents to Sustainability; iii) analyzes of publications derived from dissertations to identify which "green" dissertations were published in books, events and journals and vi) interviews with coordinators of the programs to identify concepts of program management for Sustainability and teachers from different lines of research aimed at identify the concepts of Sustainability, teaching strategies and learning methodologies. In total, sixteen teachers and coordinators were interviewed. The results show that the pedagogical projects of the courses are committed to issues of regionalities and sustainable issues, but when that aspect is transferred to the subjects of the courses, this query can not be measured directly. In the item analysis of dissertations, it was observed that they do not have great representation, with only 126 of the total 1813 in academic master's degrees in Administration of Rio Grande do Sul. It was also observed that the Graduate programs do not have the incentive to sustainable management and conceptions of teachers are private and are related to the line of research in which they are linked not with the Graduate program. Thus, it analyzes the scenario is still capable of improvement, such as encouraging the publication of dissertations "green", the integration of sustainable curriculum and improvements in sustainable management.